Efficiency of bioflavonoids use in cultivation of green algae in biotechnological complexes - Usenko, Oleh; Leontieva, Tetiana; Yankovska, D.O. (Problems of Environmental Biotechnology, 2021)
The use of phytolamps of the different light spectrum with the addition of bioflavonoids to the medium to obtain highly efficient strains of algae with specified characteristics was investigated.